STRATEGI INVESTASI BERBASIS RETURN PER UNIT RISK - Sugiarto Sugiarto; Anton Wachidin Widjaja; Fongnawati Budhijono; Muhammad Fuad; Januar Wahjudi (Jurnal Bina Manajemen, 2022)
This research is aimed at obtaining an industrial sector that has the ability to produce an Average Return Per Unit Risk (ARPUR) which is significantly better than the ability of other industrial sectors as a reference for implementing a return per unit risk-based investment strategy. In this study, 900 average return per unit risk data from each industrial sector index for the 2004 to 2018 observation period were used. The research data was generated from 35235 daily return data from all index sectors in the Jakarta Stock Industry Classification downloaded from the Bloomberg terminal. Data analysis was carried out using descriptive statistics, Analysis of variance and further tests. For investors who emphasize attention to the industrial sector with the best average ARPUR in determining the Return Per Unit Risk-Based Investment Strategy, attention can be paid to industrial sector 9 (JAKTRAD, Jakarta Trade, Services, and Investment) and industrial sector 6 (JAKPROP, Jakarta Construction, Property, and Real Estate) which ranks first and ranks second for the highest average ARPUR. However, based on a more comprehensive study, industrial sector 9 provides more comfort for investors because in addition to showing the highest average ARPUR performance, it also shows a lower dispersion than sector 6.